Successful treatment of malignant thymoma with sacrum metastases: A case report and review of literature - Liu, Shuzhong (Medicine (Baltimore), 2018)
RATIONALE: Malignant thymoma in the spine is a rare disease without standard curative managements so far. The objective of this article is to report a very rare case of recurrent malignant thymoma with sacrum metastases causing severe lumbosacral pain, which was presented with acute radiculopathy and treated with 2 operations combined with stabilization and cement augmentation. The management of these unique cases is not well-documented. PATIENT CONCERNS: A 75-year-old man presented with lumbosacral pain, radiating pain and numbness of the left extremity. The patient underwent thymectomy in 2008, and posterior spinal cord decompression, tumor resection and a stabilization procedure in 2011. Pathologic results confirmed malignant thymomas of the spine. Imaging studies revealed the density of soft tissues, obvious bony destruction in the sacrum, and significant spinal cord obstruction. DIAGNOSES: We believe this is a less-documented case of metastatic thymoma of the sacral spine presenting with back pain and radiculopathy, and presenting as a giant solid tumor. INTERVENTIONS: The patient underwent osteoplasty via a posterior approach. Pathologic results confirmed malignant thymomas of the sacral spine. OUTCOMES: The patient's neurological deficits improved significantly after the surgery, and the postoperative period was uneventful at the 6-month and 1-year follow-up visit. There were no other complications associated with the operation during the follow-up period. LESSONS: This article emphasizes metastatic thymoma of the spine, although rare, should be part of the differential when the patient presents with back pain and radiculopathy. We recommend the posterior approach for spinal decompression of the metastatic thymoma when the tumor has caused neurological deficits. Osteoplasty by cement augmentation is also a good choice for surgical treatment.